Analisis Faktor-faktor yang Mempengaruhi Tingkat Pengangguran di Provinsi Kalimantan Selatan Periode 2011-2020 - Anggit Budiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research was conducted to analyze the effect of the Population Growth Rate, Economic Growth, and Inflation both partially and simultaneously on the Unemployment Rate in South Kalimantan Province in 2011-2020. The type of research used is a quantitative approach. With data analysis used in the form of Time Series data. Meanwhile, the data used comes from the official website of the Central Statistics Agency (BPS). The results of the study show that, simultaneously, it has a significant effect on the Unemployment Rate. Then, partially the Population Growth Rate and Inflation have a significant effect, Economic Growth has no significant effect on the Unemployment Rate in South Kalimantan Province in 2011-2020.